PERAN HUMAS RUMAH SAKIT ISLAM IBNU SINA DALAM MELAKSANAKAN MISI PELAYANAN KESEHATAN YANG PRIMA DAN ISLAMI DI PEKANBARU - Suci Adhiani; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Ibnu Sina Hospital is the Islamic Hospital in Pekanbaru in the field of work processes based on Islamic Shari'a Shari'a. PR Ibnu Sina Hospitals reflect the image and role is to embody the image of the Prima Hospital and Islamic. PR Ibn Sina Hospital Pekanbaru have never had a bad problem in terms of dealing with customers, media, and government. Because according to the hospital management, the PR must maintain a good relationship with these parties.The method used in this study is a qualitative method approach to systems theory. Data were collected through observation, interviews, and documentation. Informants contained in this study consists of four seven people were determined by purposive sampling.Results of research Role of Public Relations of the Ibnu Sina Hospital Pekanabaru in realizing the vision and mission of Ibn Sina Hospital which makes Hospitals are primed and Islami, conducted activities that reflect Houses hurt slam prime and Islamic as well as to maintain the image of Ibn Sina Hospital itself. The following activities or the activities of the Hospital Staff.Keyword : Ibnu Sina’s Public Relations, the prima and islamic hospital